IT-forensik i brottmål. En studie om IT-forensiker som expertvittne. - Bjerkborn,Linn (2025)
This thesis is made in cooperation with NFC (Nationellt Forensiskt Centrum), the national forensic department of the Swedish Police Authority. It examines how IT forensic experts act in their role as expert witnesses in Swedish criminal cases, with a focus on rule of law. Using an ideal model as a theoretical starting point, in which objectivity and communication of uncertainties are central, 21 actual witness statements are analysed. The thesis seeks to answer how well these testimonies correspond to the ideal image and what recurring patterns can be discerned in practice. The study shows that many IT forensic experts behave professionally in their role. They stay within their area of expertise, avoid legal assessments and express themselves with technical restraint. This strengthens confidence in the expert´s role in the process. At the same time, several shortcomings are identified, such as the fact that the choice of method, sources of error and uncertainties are rarely reported in oral testimony and that there are extensive communication difficulties between the witness and the parties. In several cases, the expert´s statement appears to be a technical truth rather than an analysis with limitations and reservations. In the long run, this can reduce the court´s ability to make an independent assessment. The thesis also highlights how IT forensic experts in the role of the expert witness often shifts from analyst to educator. Instead of nuancing the significance of the evidence, the testimony is used to explain technical concepts to the court. This is partly understandable, but risks overshadowing the critical analysis that should be the core task of expert witnesses. Communication difficulties between IT forensic experts and court actors are common and affect the impact of evidence. Furthermore, the use of expert witnesses is selective. They are mainly heard in cases involving child pornography offences, even though digital evidence is common in other types of crime.
Keywords: allmän rättslära; bevisrätt; processrätt; IT-forensik; expertvittne; straffrätt; rättsvetenskap